Optimizing the Use of Digital-Based Learning Media Against Numerical Literacy - Arie Purwa Kusuma; Nurina Kurniasari Rahmawati; Haris Hamdani (FOUNDAE (Foundation of Advanced Education), 2022)
The COVID-19 pandemic has necessitated a shift from offline to online learning systems, requiring all sectors of education to adapt swiftly to these changes. However, the transition to online learning has presented challenges, particularly in maintaining student engagement, comprehension, and numeracy literacy skills. Field data reveals that many teachers have not fully optimized the use of digital-based learning media to enhance numeracy literacy among students. Recognizing this gap, STKIP Kusuma Negara, in collaboration with the PKM Team, conducted a community service initiative at SD Negeri Srijaya 04 Bekasi. The primary objective of this initiative was to assist teachers in optimizing the use of digital technology in their teaching practices to improve students' numeracy literacy. The PKM program was implemented through a series of activities including socialization, introduction to digital tools, training sessions, and practical applications of numeracy literacy. The results of this initiative indicate an improvement in teachers' ability to integrate digital media into their teaching, leading to enhanced numeracy literacy skills among students through effective technology adaptation